Boredom in Online Language Classrooms: Vietnamese EFL Students' Perspectives - Sieu Khai Luong (IGI Global, 2024)
This study investigates the causes of and suggested solutions to students' boredom in online EFL learning in Vietnam during Covid - 19. The study follows descriptive qualitative research design with the use of semi-structured interview as the sole instrument. Due to the social distance, online interviews with 38 student participants were conducted via Google Meet. Findings show that among the three factors (teacher-related, IT-related, and task-related), the teacher-related factors were the leading causes of students' boredom. Likewise, most of the students' suggestions to mitigate boredom are teacher-related: teachers' IT competency, interactive classrooms, real-life task types and authentic materials, games, bonus points, teachers' and students' relationships. On that basis, the study recommends teachers' training to improve online instruction, not only while but also post-Covid – 19 area because remote teaching using technology is an unavoidably rising trend in modern society.